2019
DOI: 10.1155/2019/4387636
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Anthropometric Equations to Estimate DXA-Derived Skeletal Muscle Mass in Professional Male Soccer Players

Abstract: Background Several anthropometric equations that estimate skeletal muscle mass (SMM) have been published, but their applicability and accuracy among athletes are still uncertain. Purpose To assess the accuracy of different anthropometric equations that estimate SMM in professional male soccer players, as compared to dual-energy X-ray absorptiometry (DXA) as the reference method. Methods In this cross-sectional study, we evaluated 179 professional male soccer players aged between 18 and 37 years. Anthropometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Skeletal muscle mass (SMM) is the largest component of the adipose tissue-free body mass in humans [ 5 ], essential for athletic performance. Despite many differences in training and competition specificity, available research indicates that SMM content in athletes ranges from 40% to 48% of total body mass [ 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle mass (SMM) is the largest component of the adipose tissue-free body mass in humans [ 5 ], essential for athletic performance. Despite many differences in training and competition specificity, available research indicates that SMM content in athletes ranges from 40% to 48% of total body mass [ 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the most commonly used equations are (a) Durnin and Womersley (1974) for sedentary population; (b) Jackson and Pollock (1978), Jackson et al (1980), Harbin et al (2017) for physically active men and women; and (c) Yuhasz (1962) or Faulkner (1968) for sub-elite and elite athletes. However, anthropometrists should be aware of the recent validation studies (compared to DXA), which have revealed new equations for different populations, such as Caucasian young male and female football players (Lozano-Berges et al, 2019), international soccer players of the Italian Serie-A (Nunez et al, 2019), professional Mexican male soccer players (Gonzalez-Mendoza et al, 2019), Spanish elite youth male soccer players (Munguía-Izquierdo et al, 2018), Japanese male athletes (Takai et al, 2018), Colombian adult women (Aristizabal et al, 2018), physically active women and men (Lahav et al, 2018), southern Brazilian adolescents (Ripka et al, 2017), Italian female handball players (Cavedon et al, 2018), and young Iranian wrestlers (Riyahi-Alam et al, 2017). In “fitness” and bodybuilding, the success and achievement of goals can be accounted for in large part by easily obtained physical variables, as Fry and colleagues (Fry et al, 1991) demonstrated after they analyzed anthropometric features as discriminators of success in North American bodybuilders.…”
Section: Resultsmentioning
confidence: 99%
“…Body fat (%) was estimated using standard equation (Siri 1956); formula was used to calculate density (Durnin and Womersley 1974). Skeletal muscle mass (kg and %) was estimated based on standard formula (Lee et al 2000) that has been validated by a previous study in Mexico and showed best agreement with the results obtained using dual-energy X-ray absorptiometry (DXA) (González-Mendoza et al 2019). Somatotype rating was done using standard references (Carter and Heath 1990).…”
Section: Methods and Participantsmentioning
confidence: 99%